1981
DOI: 10.1136/thx.36.11.828
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma in a factory making flux-cored solder containing colophony.

Abstract: The prevalence of work-related wheeze and breathlessness was measured in factory employees manufacturing flux-cored solder. The flux contained colophony which was heated in the production process, exposing the workers to colophony fumes. Measurement of colophony in the breathing zone defined three grades of exposure with median levels of 1-92 mg/i3 (six subjects), 0-02 mg/m3 (14 subjects), and less than 0O01 mg/m3 (68 subjects). All but two workers in the first two groups, and 90 % of a random sample of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 9 publications
2
17
0
1
Order By: Relevance
“…A man aged 50 yrs developed obstructive airways disease after exposure to high concentration of ammonia vapours [136]. Several other studies of the sequelae of chlorine gas exposure showed similar findings [137,138].…”
Section: Reactive Airways Dysfunction Syndrome (Rads)supporting
confidence: 67%
“…A man aged 50 yrs developed obstructive airways disease after exposure to high concentration of ammonia vapours [136]. Several other studies of the sequelae of chlorine gas exposure showed similar findings [137,138].…”
Section: Reactive Airways Dysfunction Syndrome (Rads)supporting
confidence: 67%
“…Restrictions in lung function and obstructive respiratory diseases have been described especially after longer term exposure to abietic acid or its oxidation and decomposition products in vapours of soldering fluxes containing rosin (see also documentation "Rosin (colophony)" 1998, supplement "Rosin" 2013; Burge 1982Burge , 1984Burge et al 1980Burge et al , 1981Palmer and Crane 1997;Pengelly et al 1998 b) or during the manufacture of soldering fluxes containing rosin (temperature >140°1 C) (Burge et al 1981). Such symptoms also occurred after exposure to vapours of hot-melt adhesives based on rosin (Fawcett et al 1976;, unheated rosin dust (Burge et al 1986), heated rubber chemicals (Tarlo 1992), pinewood dust containing abietic and pimaric acid (Ayars et al 1989;Teschke et al 1999;Whitehead et al 1981), aerosols of aw ater-miscible coolant (Hendy et al 1985) or cleaning agents containing rosin (McCoach et al 1999).…”
Section: Sensitizing Effects On the Airwaysmentioning
confidence: 99%
“…The duration of latency seems to depend on the nature of the causal agent, and exposure duration and intensity to a sensitizing agent. [15][16][17][18][19][20] In subjects with occupational asthma caused by high molecular weight agents, the latent period was longer than in those caused by low molecular weight agents. In the latter instance, 50% of patients develop symptoms within the first 2 years of exposure.…”
Section: Discussionmentioning
confidence: 99%